Geldsicherheit und stabilere Finanzen durch Vollgeld - Joseph Huber (IBF - Institut für Bank- und Finanzgeschichte, 2017)
– The following article presents the concept of the sovereign money system. The term 'sovereign money' (Vollgeld in German) refers to unrestricted legal tender, issued by a monetary authority such as a central bank. In contrast to bank deposit money, sovereign money-on-account for public use among non-banks is a fundamental prerequisite for achieving safe and secure money, more stable finances, and a better balanced money supply for the entire economy. Historically, sovereign money has existed in the form of precious metal coins. Today, sovereign money exists as cash in the form of treasury-issued secondary coins and central bank notes, likewise as non-cash central bank funds, the so-called reserves. These, however, are for interbank payment transactions only, non-available for public use among non-banks. The major means of payment for non-banks is bank deposit money. The credit balances on deposit accounts are created in the course of bank lending to non-bank customers, or purchasing assets from them. Bank deposit money is not legal tender, but a promissory credit entry to convert the balance into cash on customer demand, or transfer the balance to other customer accounts by way of clearing and transfer of reserves. Bank deposit money thus references another monetary base in the form of cash and central bank reserves, whereby these cover only a small fraction of the supply of bank deposit money. Sovereign money, by contrast, is modern fiat money in its own right, part of the monetary base, not a surrogate relating to a fractional or full base of gold, cash, or reserves.
Keywords: E42; E52; 330